Religiosity in Work Motivation and Performance Quality among the LGBT Community in Gorontalo: A Perspective of Sociology of Religion and Social Formation - Wibawa, Nazar Husain Hadi Pranata; Rahmawati (LPPM IAIN Parepare, 2024)
This study aims to find out the implications of religiosity behavior on work motivation in LGBT people in Gorontalo and religious behavior has implications for improving the work quality of LGBT people in Gorontalo. The subject of this study is the LGBT community in Gorontalo City and Muslims, they already have an official community with comprehensive management and personal structure. This LGBT community is obedient and consistent in the bond of vision and mission that they have agreed upon. The type of research used is qualitative descriptive using a religious approach, and a sociological <span id=